Ordered intermetallic Pt-Fe nano-catalysts for carbon monoxide and benzene oxidation. (March 2018) - Saravanan, Govindachetty; Jayasree, K. Pulleri; Divya, Yearwar; Pallavi, Mungse; Nitin, Labhsetwar
Abstract: Conversion of toxic, indoor pollutants into innocuous products through catalytic reaction is one of the promising among other permanent solutions. γ-Al2 O3 supported, Pt-based intermetallic nanoparticles (NPs) using abundantly available metal e.g., Fe (Pt-Fe; Pt3 Fe and PtFe3 ) as catalysts are successfully prepared through a wet-impregnation method followed by calcination in the presence of H2 at 800 °C. Although the intermetallic Pt-Fe NPs are prepared at elevated temperatures, they are, however, not agglomerated and are finely dispersed on the γ-Al2 O3 support with the average particle size between 4 and 6 nm. No other intermetallic or alloy phases of Pt-Fe were not observed under the set synthesis conditions. Despite the same Pt-mass loading in the both Pt-Fe catalysts, intermetallic PtFe3 catalysts showed much improved carbon monoxide (CO) oxidation activity by at least 8-fold compared to that of the intermetallic Pt3 Fe catalysts. The intermetallic PtFe3 catalysts showed the enhanced activity for CO oxidation compared to that of the intermetallic Pt3 Fe catalysts, however, both the intermetallic Pt-Fe catalysts showed virtually the same catalytic activity for benzene oxidation. Both the intermetallic Pt-Fe catalysts showed the stable, multi-cycle catalytic performance for the catalytic CO and benzene oxidation and retain their structure and morphology even after catalytic reaction. Highlights: Intermetallic Pt-Fe catalysts showed the promise for indoor air treatments. Intermetallic Pt-Fe catalysts showed the enhanced catalytic activity for indoor pollutants. Intermetallic Pt-Fe catalysts showed the stable and multi-cycle catalytic performance. Structure and morphology of the intermetallic Pt-Fe catalysts are retained even after catalysis.